‘I’m not burning out, I’m rusting out’: investigating the causes of rustout in teacher educators in Ireland and the United Kingdom - Sabrina Fitzsimons; David S. Smith (Humanities & Social Sciences Communications)
Abstract Higher Education-Based Teacher Educators (TEs) are responsible for the preparation of future teachers across the continuum of education. However, despite their significant role in the education ecosystem, their well-being and professional satisfaction often remain overlooked in research and policy. For example, while burnout among academics is extensively studied, it remains under-researched, particularly among TEs. Even less attention is paid to rustout, a phenomenon characterised by professional underutilisation, intellectual stagnation and unfulfillment. Rustout is not a universal experience. However, its presence acknowledges that occupational stress is non-linear and nuanced and that it can vary depending on organisational and personal resources. Like its better-known counterpart, burnout, untreated rustout can have individual and organisational consequences, such as poor mental health, career dissatisfaction and accelerated employee turnover. Through an analysis of surveys and interviews with TEs across Ireland and the United Kingdom (UK), we explore the factors that may contribute to rustout. Guided by rustout literature and validated through collaborative reflection, this paper reveals three core themes: (1) administrative overload and erosion of autonomy, (2) misalignment between professional aspirations and job tasks and (3) systemic barriers to professional growth. Some participants reported being ‘prevented from thriving’, while others actively sought ways to mitigate rustout through new challenges or external opportunities. More broadly, the study shines a light on the ‘silence’ surrounding rustout in academia. The findings also highlight the detrimental effects of rustout on individual well-being and suggest that it is not merely a pre-retirement phenomenon but can emerge at various stages of a TE’s career. Practical implications emphasise the need for Higher Education (HE) sectors and leaders to put ‘rustout’ on the mental health literacy agenda, to balance job demands with resources and to acknowledge the trade-off that can occur when operational efficiency is prioritised over professional well-being.